1981
DOI: 10.1097/00006842-198102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Talking on the Blood Pressure of Hypertensive and Normotensive Individuals

Abstract: The use of a recently developed noninvasive automated blood-pressure device has revealed a striking relationship between human communication and elevations in blood pressure in both normotensive and hypertensive individuals. Individuals with higher resting baseline pressures tended to show greater increases during talking than did those with lower pressures. In some hypertensive individuals increases blood pressure greater than 25-40% occurred within 30 sec after the initiation of human speech. Links between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 23 publications
6
43
0
1
Order By: Relevance
“…It appears that the higher the resting value of blood pressure, the greater the rise in blood pressure. So the increase in blood pressure in hypertensive individuals when they are talking is greater than that in normotensive individuals (Lynch et al, 1981). The extent of the reaction appears to be comparable with that of a regular exercise stress test (Thomas et al, 1992), does not change as a result of the use of antihypertensives (Dimsdale et al, 1992) and occurs both in an experimental and a medical setting (Lynch et al, 1982).…”
Section: Verbal Activitymentioning
confidence: 98%
“…It appears that the higher the resting value of blood pressure, the greater the rise in blood pressure. So the increase in blood pressure in hypertensive individuals when they are talking is greater than that in normotensive individuals (Lynch et al, 1981). The extent of the reaction appears to be comparable with that of a regular exercise stress test (Thomas et al, 1992), does not change as a result of the use of antihypertensives (Dimsdale et al, 1992) and occurs both in an experimental and a medical setting (Lynch et al, 1982).…”
Section: Verbal Activitymentioning
confidence: 98%
“…The physical act of talking has been shown to raise blood pressure (9). However, subsequent research has shown that speaking about a topic of personal relevance results in greater increases in blood pressure and greater decreases in T-wave amplitude and blood volume pulse than does producing neutral speech (10).…”
Section: Introductionmentioning
confidence: 99%
“…The state of physical inactivity and the absence of orthostatic loading associated with HDT bedrest was expected to cause an immediate attenuation of the circadian BP variability. The residual day±night variation of BP can be explained by other sources of BP variability still present when con®ned to bed, such as mental stress (James et al 1986), talking (Lynch et al 1981), micturition and defecation (Littler et al 1974) and the effect of ingested food and drink (Kelbaek et al 1989). A striking rise of BP was observed during the meals in the HDT period, which were taken while lying with the face downward and the head protruding out of the bed.…”
Section: Discussionmentioning
confidence: 99%